Long minority carrier lifetime in Au-catalyzed GaAs/AlxGa1-xAs core-shell nanowires - Jiang, N; Parkinson, P; Gao, Q; Breuer, S; Tan, H; Wong-Leung, J; Jagadish, C (2012)
GaAs/Al xGa 1-xAs core-shell nanowires were grown by metal organic chemical vapor deposition with optimized Al xGa 1-xAs shell and twin-free Au-catalyzed GaAs cores. Time-resolved photoluminescence measurements were carried out on single nanowires at room temperature, revealing minority carrier lifetimes of 1.02 ± 0.43 ns, comparable to self-assisted nanowires grown by molecular beam epitaxy. The long minority carrier lifetimes are mainly attributed to improvement of the GaAs/Al xGa 1-xAs interface quality. The upper limit of surface recombination velocity of the structure is calculated to be 1300 cm/s with the Al xGa 1-xAs shell grown at 750 °C, which is comparable with planar double heterostructures. © 2012 American Institute of Physics.